The development of unemployment in NUTS II region of Eastern Slovakia - Babiak, Radomír; Rosič, Martin (Journal for Geography, 2011)
Eastern Slovakia belongs to the most undeveloped NUTS II regions of the European Union. This region reaches high level of the unemployment rate, what together with the low production of GDP per capita forms unfavourable living conditions for its inhabitants. This article studies the development of the unemployment rate and the partial structures of unemployment in the region. It identifies key factors which affect the unemployment. It turns the attention to the potential of the region in the fight against the unemployment, from the point of view of its macro-regional and meso-regional position in the European space. It identifies specific subregions within the Eastern Slovakia and analyses its intraregional disparities in the context of labour market stability.
Keywords: eastern Slovakia; unemployment; unemployment rate